A Dancer in Syria - Rigsby, Kent J. (Hyperboreus, 2017)
A decree of the Technitai of Dionysus, of Hadrianic date, to honor a pantomimos who was a high priest is not evidence that these performers were members of the Actors’ guild, which honored many people. His priesthood may well be proof of a guild of dancers at this early date (so N. A. Almazova), and if he also served thus for the Technitai on this occasion, that would be via their ad hominem grant.